The impact of cross border mergers and acquisitions on the operating financial and short - term share price performance of acquiring companies listed on the Johannesburg Stock Exchange - Thaver, Kuben (University of Pretoria, 2014)
Dissertation (MBA)--University of Pretoria, 2013.